Determination of the apparent variability and inheritance of chlorophyll content and some vegetative growth characteristics in the bread wheat (Triticum aestivum L.) Cham-6 - under the effect of the pre-planting - Mohammed Ayoub; Arwa Al - Zubaidi (College of Education for Pure Sciences, 2019)
Glycine Betain (GB) solution at concentration of (0.08 M) was used for soaking grains of bread wheat variety (Sham-6-) for (0 hours, 6 hours, 12 hours) before sowing to evaluate the effect of (GB) on phenotypic variances and heritability of the characters ; plant height, number of leaves after one month of germination, flag leaf length and flag leaf area at 120 days of cultivation, total content of chlorophyll (a & b), total number of leaves and resistance to lodging. The results indicated that there were significant differences between treatments, desirable and significant increase was observed for the (6 hours) treatment. High significant differences were detected for genetic, environmental and phenotypic variances for all characters. The environmental variance was higher than genetic values. The broad sense heritability was low for plant high and number of leaves after one month of germination, flag leaf length and flag leaf area at 120 days of cultivation, total content of chlorophyll (a , b) and resistance to lodging at maturity but medium for total number of leaves.